Mechanical Behavior of a Multisegmented Tower Anchorage Structure with an Exposed Steel Anchor Box - Wenru Lu; Min Zhao; Lingling Jia (Advances in Materials Science and Engineering)
A tower anchorage structure with an exposed steel anchor box is commonly used for cable-stayed bridges. Many researchers have conducted studies on this structure by considering a single segment. However, in practical engineering, the stress of multisegmented tower anchorage structure is not completely similar to that of single segment, and the forces between segments affect each other. Hence, in this study, the mechanical behavior of a multisegment anchorage structure with an exposed steel anchor box was investigated via finite element analysis. Furthermore, the load transfer path and stress distribution characteristics of the structure were investigated. The results indicate that the horizontal component of the cable force is borne by the side plate of the steel anchor box, the diaphragm, and the side wall of the concrete tower column, while the vertical component is transmitted by the steel anchor box and concrete tower column. Under the action of this cable force, the horizontal component of the cable force borne by the middle segment increases, while the components at the two end segments decrease. The vertical force is greater on the lower tower segments. The stress levels on the side plate and on the diaphragm of the steel anchor box in the middle section are high. Under the cable force load, the frame formed by the end plate and side plate of the steel anchor box expands outward. The end plate is mainly under a tensile load, and the tensile stress level on the lower section exceeds that on the upper section. A high-stress area for the concrete tower is observed in the steel-concrete joint. The stud group of the anchorage structure is subjected to horizontal and vertical shear forces, and no “saddle-shaped” distribution of the stud shear is found. An optimal arrangement method for the stud group was proposed to optimize its mechanical performance.